Innovation in Psychotherapy, Challenges, and Opportunities: An Opinion Paper - Schweiger, Janina Isabel; Kahl, Kai G.; Klein, Jan Philipp; Sipos, Valerija; Schweiger, Ulrich (Frontiers in Psychology, 2019)
Psychotherapy as a field tends towards conservativism and the rate of innovation and development of new evidence-based effective treatments has been slow. The paper explores important barriers to innovation like the dodo-bird-verdict, the habit of starting the development of therapeutic methods from techniques. The paper looks at the opportunities for translating basic science in psychology into psychotherapeutic techniques. Metacognitive therapy stands out from other psychotherapies by its development from basic science. The paper describes the development of the techniques detached mindfulness and attention training, how they were derived from basic science and tested for their suitability in the therapy of patients with anxiety disorders. By this process metacognitive therapy may be an important model for the innovation process in psychotherapy.